2015
DOI: 10.1007/s11743-015-1682-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Succinic Gemini Surfactants and the Effect of Stereochemistry on Their Monolayer Behaviors

Abstract: In this work, succinic gemini surfactants, dl‐ and meso‐2,3‐bis(alkyl)succinic acids (alkyl: C6H13–C13H27), were successfully synthesized by oxidative coupling of enolates of fatty acid tert‐butyl esters with copper(II) bromide followed by treatment with CF3COOH. Focusing on the influence of stereochemistry (dl‐ and meso‐) of succinic geminis, their monolayer behaviors at the air–water interface were explored using surface pressure–area (Π–A) isotherms, the compression modulus of monolayers (εs), and Brewster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the case of the hydrocarbon geminis dl-and meso-C11 , although the values of A L were same for both isomers, dl-and meso-C11 exhibited completely different π-A isotherms 16 . That is, as shown in Fig.…”
Section: Effect Of Stereochemistrymentioning
confidence: 82%
See 3 more Smart Citations
“…In the case of the hydrocarbon geminis dl-and meso-C11 , although the values of A L were same for both isomers, dl-and meso-C11 exhibited completely different π-A isotherms 16 . That is, as shown in Fig.…”
Section: Effect Of Stereochemistrymentioning
confidence: 82%
“…In our previous work on dl-and meso-C11 16 , it was concluded that the two hydrophobic alkyl groups were in an almost upright orientation, with the hydrophobic and hydrophilic groups set in an eclipsed conformation across the carbon-carbon bond of the gemini spacer. In the meso-isomer, the two hydrophobic alkyl chains were parallel to each other across the carbon-carbon bond of the gemini spacer, while those of the dl-isomer were set in a skewed position.…”
Section: Effect Of Semifluoroalkyls On a Lmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have reported the synthesis of 2,3-bis undecyl succinic acid, an all-hydrocarbon gemini. This gemini is formed by having two vicinal COOH head groups attached directly to the gemini platform by the interconversion of an OH group of corynomicolic acid to a COOH group 27,31 . Moreover, the effect of stereochemistry mesoand dl-of the two COOH groups of the succinic acid gemini surfactant on its properties was studied.…”
Section: Introductionmentioning
confidence: 99%